Teburu—Open source 3D printable bioreactor for tissue slices as dynamic three‐dimensional cell culture models. Issue 10 (17th July 2019) - Daneshgar, Assal; Tang, Peter; Remde, Christopher; Lommel, Michael; Moosburner, Simon; Kertzscher, Ulrich; Klein, Oliver; Weinhart, Marie; Pratschke, Johann; Sauer, Igor M.; Hillebrandt, Karl H.
Abstract: Three‐dimensional tissue cultures are important models for the study of cell‐cell and cell‐matrix interactions, as well as, to investigate tissue repair and reconstruction pathways. Therefore, we designed a reproducible and easy to handle printable bioreactor system ( Teburu ), that is applicable for different approaches of pathway investigation and targeted tissue repair using human tissue slices as a three‐dimensional cell culture model. Here, we definitively describe Teburu as a controlled environment to reseed a 500‐µm thick decellularized human liver slice using human mesenchymal stroma cells. During a cultivation period of eight days, Teburu, as a semi‐open and low consumption system, was capable to maintain steady pH and oxygenation levels. Its combination with additional modules delivers an applicability for a wide range of tissue engineering approaches under optimal culture conditions.